Dysregulation of human apurinic/apyrimidinic endonuclease 1 (APE1) expression in advanced retinoblastoma. Issue 3 (2nd January 2014) - Sudhakar, Job; Khetan, Vikas; Madhusudan, Srinivasan; Krishnakumar, Subramanian
Abstract : Background: Retinoblastoma (RB) is a childhood eye tumour. Dysregulation of DNA repair may not only influence pathogenesis but could also adversely impact on response to cytotoxic chemotherapy frequently used in RB therapy. We studied the expression of human apurinic/apyrimidinic endonuclease (APE1), a key multifunctional protein involved in DNA base excision repair in RB. Methods: Expression of APE1 was evaluated by immunohistochemistry in a series of 55 RBs and in retina. In tumours, APE1 expression was analysed in cytoplasm and nucleus independently and correlated with histopathological features, including invasion, differentiation and International Intraocular Retinoblastoma Classification groups. Relative APE1 mRNA and protein expressions were evaluated by real-time PCR and western blot. The expression of APE1 in tumour groups was compared with retinal tissue. Results: APE1 cytoplasmic expression was observed in 98% and nuclear positivity was observed in 83% of tumours analysed. Tumour cells invading the optic nerve showed predominant cytoplasmic immunoreactivity. An inverse correlation between cytoplasmic and nuclear positivity was observed. Real-time PCR revealed an increase in APE1 transcripts compared with retina. Western blot revealed a decreased protein concentration compared with retinal tissue. Conclusions: This is the first study of APE1 expression in RB. Our observation suggests that subcellular localisation of APE1 is altered in RB. APE1 could be a potential drug target in RB.